Influence of rafted microstructures on creep in Ni-base single crystal superalloys: a 3D discrete dislocation dynamics study. (27th December 2019) - Gao, Siwen; Ali, Muhammad Adil; Hartmaier, Alexander
Abstract: Ni-base single-crystal superalloys exhibit a dynamic evolution of their microstructure during operation at elevated temperatures. The rafting of γ ′ precipitates changes the mechanical behavior in a way that was understood insufficiently. In this work, we combine a phase-field method with a discrete dislocation dynamics model to clarify the influence of different rafted microstructures with the same initial dislocation density and configuration on creep behavior. The unrafted and rafted microstructures of Ni-base single crystal superalloys are simulated by a phase-field crystal plasticity method. By introducing these microstructures into a 3D discrete dislocation dynamics (DDD) model, the creep behavior under uniaxial loads of 350 and 250 MPa along [100] direction at 950 °C is studied. Due to the negative lattice mismatch of Ni-base superalloys, the N-type rafting with the formation of plate-like γ ′ precipitates occurs under uniaxial tensile loads along 100 direction at high temperatures, while the P-type rafting with the formation of rod-like γ ′ precipitates occurs under compressive loads. Taking the cuboidal, N-type rafted and P-type rafted microstructures as the initial and fixed microstructures for the same loading conditions, it is found from DDD simulations that the rafted microstructures result in smaller creep deformation than the cuboidal microstructure. The reason for this is that the coalescence of γ ′ precipitates during the rafting diminishes the width of some γ channels, so as to increase the local Orowan stresses which retard the dislocation glide. For tensile loads, the N-type rafted microstructure has the best creep resistance. For a low compressive load, the P-type rafting shows a better creep resistance than N-type rafting.